2009
DOI: 10.1007/s11120-009-9455-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal genomes, maximal productivity: comparative genomics of the photosystem and light-harvesting complexes in the marine cyanobacterium, Prochlorococcus

Abstract: Although Prochlorococcus isolates possess the smallest genomes of any extant photosynthetic organism, this genus numerically dominates vast regions of the world's subtropical and tropical open oceans and has evolved to become an important contributor to global biogeochemical cycles. The sequencing of 12 Prochlorococcus genomes provides a glimpse of the extensive genetic heterogeneity and, thus, physiological potential of the lineage. In this study, we present an up-to-date comparative analysis of major protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
2
6
0
1
Order By: Relevance
“…This is remarkable because it suggests that a given environment tends to select for a particular optimal genome size range, even across distinct lineages; furthermore, it suggests that lineages spend sufficient time in their preferred environments to allow for these optimal genome sizes to be selected for and maintained (against a mutational spectrum that is thought to be largely biased toward deletions in bacteria) (Mira et al 2001;Nilsson et al 2005). Our observation confirms what has been known anecdotally from a number of environments: Planktonic marine environments, for example, persistently select for small to very small genome sizes (Giovannoni et al 2005;Ting et al 2009), whereas soil microbes are often among those with the largest genomes. Our results are also in line with observations indicating different average genome sizes in distinct environments Angly et al 2009).…”
Section: à13supporting
confidence: 80%
“…This is remarkable because it suggests that a given environment tends to select for a particular optimal genome size range, even across distinct lineages; furthermore, it suggests that lineages spend sufficient time in their preferred environments to allow for these optimal genome sizes to be selected for and maintained (against a mutational spectrum that is thought to be largely biased toward deletions in bacteria) (Mira et al 2001;Nilsson et al 2005). Our observation confirms what has been known anecdotally from a number of environments: Planktonic marine environments, for example, persistently select for small to very small genome sizes (Giovannoni et al 2005;Ting et al 2009), whereas soil microbes are often among those with the largest genomes. Our results are also in line with observations indicating different average genome sizes in distinct environments Angly et al 2009).…”
Section: à13supporting
confidence: 80%
“…These insertions involve genes of unknown function (P9303_08061, P9303_08111), as well as a predicted pseudogene (annotated as a pseudogene derived from P9313_15181). Furthermore, as our laboratory (Ting et al 2009) and as others (Roberts et al 2012) have reported, deeply branched Prochlorococcus strains (SS120, MIT9211, NATL2A, NATL1A, MIT9313, MIT9303) retain an additional putative carboxysome gene (csoS1E) which is located directly downstream of csoS4B (Fig. 2).…”
Section: Genomic Organization Of Ccm Componentssupporting
confidence: 54%
“…The annotated files containing the complete genome sequences of 12 Prochlorococcus strains (MIT9312, MED4, MIT9515, MIT9301, MIT215, AS9601, SS120, MIT9211, NATL1A, NATL2A, MIT9303, MIT9313), as well as other cyanobacteria, were extracted from GenBank (http://www.ncbi.nlm.nih.gov) and were used in constructing our in-house database system as described in Ting et al (2009). Gene and protein sequences for specific CCM components were extracted from our in-house database, GenBank (http://www.ncbi.nlm.nih.gov), and Cyanobase (http://genome.microbedb.jp/cyanobase/).…”
Section: Genome Sequence Data and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A cianobakteriális PSII szerkezete csak két termofil faj esetén ismert atomi szinten, ezért annak univerzalitása a rendkívül széles körű diverzitást mutató cianobaktériumok között kétséges. A cianobakteriális PSII szerkezet nagyfokú plaszticitására utal a Prochlorococcus nemzetség tagjain elvégzett genom analízis, melyből fény derült olyan cianobaktérium fajok létezésére is, amelyek PsbU és cit c550 PSII alegységeket kódoló géneket nem tartalmaznak (39). …”
Section: Egyedülálló Cit B559 Kifejeződésunclassified